STUDY OF PHYSICAL PARAMETERS AND HABITABILITY OF THE TEEGARDEN PLANETARY SYSTEM - Rahman, Riki
The discovery of planets beyond our Solar System, also known as exoplanets, has progressed rapidly. More than 5000 exoplanets have been confirmed to date. In 2019, the existence of two exoplanets orbiting the Teegarden star, namely Teegarden b and c, was confirmed. Both exoplanets are Terrestrial planets with masses and radii are similar to Earth, so they are classified as Super Earth exoplanets. Both exoplanets were detected through radial velocity observations by the CARMENES (Calar Alto high-Resolution search for M dwarfs with Exoearths with Near-infrared and optical Echelle Spectrographs) mission from 2016 to 2019. Models in the Habitable Zone Gallery show that Teegarden b and c reside in the Teegarden’s habitable zone. This implies that there is potential for life there and was followed up with some examinations of several parameters related to habitability, including: the influence of tidal forces, especially the Tidal Locking Radius, the Roche Limit, the Classical Habitable Zone, and also biohabitability comprising atmospheric density, temperature and surface pressures. The examination makes use of the analogous approaches with those of Venus, Earth and Mars. The results of this study found that both exoplanets remain in their habitability states for a long time. It is strongly suggested that Teegarden b has a thin atmosphere like Mars, but with a higher temperature than Mars. Teegarden c has a thinner atmosphere with a lower temperature than Earth.